Efficiency of Aerial Drones for Macrolitter Monitoring on Baltic Sea Beaches - Escobar-Sánchez, Gabriela; Haseler, Mirco; Oppelt, Natascha; Schernewski, Gerald (Frontiers in Environmental Science, 2021)
Marine litter is a global problem that requires soon management and design of mitigation strategies. Marine litter monitoring is an essential step to assess the abundances, distributions, sinks and hotspots of pollution as well as the effectiveness of mitigation measures. However, these need to be time and cost-efficient, fit for purpose and context as well as provide a standardized methodology suitable for comparison among surveys. In Europe, the Marine Strategy Framework Directive (MSFD) provides a structure for the effective implementation of long-term monitoring. For beaches, the well-established 100 m OSPAR macrolitter monitoring exists. However, this method requires a high staff effort and suffers from a high spatio-temporal variability of the results. In this study, we test the potential of aerial drones or Unmanned Aerial Vehicles (UAVs) together with a GIS-based approach for semi-automatic classification of meso- (1 - 25 mm) and macrolitter (>25 mm) at four beaches of the southern Baltic Sea. Visual screening of drone images in recovery experiments (50 m2 areas) at 10 m height revealed an accuracy of 99%. The total accuracy of classification using object-based classification was 45 - 90% for the classification with 4 classes and 50 - 66% for the classification with 6 classes, depending on the algorithm and flight height used. On 100 m beach monitoring transects the accuracy was between 39 - 74% (4 classes) and 25 - 74% (6 classes), with very low kappa values, indicating that the GIS classification cannot be regarded as a reliable method for the detection of litter in the Southern Baltic. In terms of cost-efficiency, the drone showed high reproducibility and moderate accuracy, with much lower flexibility and quality of data than a comparable spatial-OSPAR method. Consequently, our results suggest that drone based monitoring cannot be recommended as a replacement or complement existing methods in southern Baltic beaches. However, other methods for image analysis and sites should be tested to explore this tool for fast-screening of non-accessible sites, fragile ecosystems, floating litter or heavily polluted beaches.